1996
DOI: 10.1146/annurev.soc.22.1.271
|View full text |Cite
|
Sign up to set email alerts
|

What Do Interlocks Do? An Analysis, Critique, and Assessment of Research on Interlocking Directorates

Abstract: Research on interlocking directorates has gained increasing prominence within the field of organizations, but it has come under increasing criticism as well. This chapter presents an in-depth examination of the study of interlocking directorates. I focus initially on both the determinants and the consequences of interlocking directorates, reviewing alternative accounts of both phenomena. Special attention is paid to the processual formulations implied by various interlock analyses. I then address the two prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,010
1
151

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,418 publications
(1,175 citation statements)
references
References 65 publications
13
1,010
1
151
Order By: Relevance
“…We tested our theoretical perspective with a unique data set that combines archival reports with primary behavioral data obtained through surveys of Forbes 1000 outside directors and GEOs. The theoretical perspective and empirical analysis presented here may help answer recent calls for research that examines the "substantive context" of board appointments (Nohria, 1992: 14) and moves our understanding beyond the simple number of such appointments or director independence as predictors of board influence and decision making (Mizruchi, 1996;Pettigrew, 1992;Stinchcombe, 1990).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We tested our theoretical perspective with a unique data set that combines archival reports with primary behavioral data obtained through surveys of Forbes 1000 outside directors and GEOs. The theoretical perspective and empirical analysis presented here may help answer recent calls for research that examines the "substantive context" of board appointments (Nohria, 1992: 14) and moves our understanding beyond the simple number of such appointments or director independence as predictors of board influence and decision making (Mizruchi, 1996;Pettigrew, 1992;Stinchcombe, 1990).…”
mentioning
confidence: 88%
“…This work demonstrates how the involvement of directors on other boards provides an important source of information about business practices and policies (cf. Mizruchi, 1996;Palmer, Jennings, & Zhou, 1993). For example, Useem (1982) observed that executives use their board appointments as a way to scan the environment for timely and pertinent information.…”
Section: Director Appointments and Board Involvement In Strategic Decmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora as preocupações se centrassem na "estrutura do mundo dos negócios", as análises apresentaram evidentes contribuições para o entendimento do poder em nossas sociedades, dialogando explícita e implicitamente com as explicações marxista e elitista para os processos de reprodução social. Nessa tradição inscrevem-se desde o já clássico Mintz e Schwartz (1981) até Mizruchi (1996) Knoke (1987). O estudo partia, em especial, de elementos presentes no pluralismo, mas pretendia "desenvolver uma abordagem mais informada sociologicamente sobre a comportamento dos grupos de interesse" (Laumman e Knoke, 1987, p.7).…”
Section: Redesunclassified
“…Corporate boards and the networks they create play a role, we argue, in both reflecting and shaping bank strategy. Board interlocks have been shown to affect strategies among a wide range of non-financial corporations, from acquisitions (Haunschild, 1993) to takeover defense policies (Davis, 1991) to philanthropy and political activity (see Mizruchi, 1996 for a review of the literature on interlocks). These effects may be even more pronounced among banks.…”
Section: Theoretical Considerationsmentioning
confidence: 99%